ATOP - Syd Bauman; Martin Holmes; Helena Bermúdez Sabel; David Maus (Journal of the Text Encoding Initiative)
The TEI XSL Stylesheets codebase is a tool that tackles the transformation of TEI XML documents to and from various formats. This includes the crucial activity of generating schemas from TEI ODD, the TEI XML–conformant specification format that allows one to write a schema language (for example, TEI P5 itself is written in ODD) or to customize TEI P5 using a literate programming approach. Because of the difficulties of maintaining this current set of stylesheets, a task force was created with the mission of developing, from scratch, an ODD processor that reads in a series of one or more TEI ODD customization files, merges them with a TEI language (likely, but not necessarily, TEI P5 itself), and generates RELAX NG and Schematron schemas. This paper presents a rationale for this task and the initial steps of this work.